Association Between Calcium Intake Adequacy and Blood Pressure Among Pregnant Women: A Cross-Sectional Study in Makassar - Sitti Nurana; Fadil Abdillah Arifin (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2026)
Hypertensive disorders of pregnancy remain a major cause of maternal morbidity and mortality worldwide. Inadequate calcium intake has been identified as a modifiable risk factor associated with elevated blood pressure during pregnancy. This study aimed to examine the association between calcium intake adequacy and blood pressure among pregnant women attending the Rappokalling Health Center, Makassar. This analytical observational study employed a cross-sectional design involving 50 pregnant women selected through accidental sampling. Calcium intake adequacy was assessed using a structured dietary questionnaire based on recommended daily calcium intake, while blood pressure was measured using a calibrated sphygmomanometer during antenatal care visits. Data were analyzed using the Chi-square test with a significance level of p < 0.05. The results showed that 50.0% of respondents had adequate calcium intake and 50.0% had inadequate intake. Most participants (70.0%) had normal blood pressure, while 30.0% had abnormal blood pressure. All pregnant women with adequate calcium intake had normal blood pressure (100.0%), whereas 60.0% of those with inadequate calcium intake experienced abnormal blood pressure. Statistical analysis revealed a significant association between calcium intake adequacy and blood pressure (p < 0.001). Adequate calcium intake was significantly associated with normal blood pressure during pregnancy. Strengthening nutritional counseling and calcium supplementation during antenatal care may help prevent hypertensive disorders of pregnancy.